Realization of 3D Electromagnetic and Thermal Analyzes of the Autotransformer by Finite Elements Method (International Journal of Engineering and Computer Science, 2018)
The aim of this work is to verify a three-phase autotransformer by reviewing it magnetically and thermally with modern software using the finite element method. For this, Ansys software uses two modules combined with Ansys Maxwell-3D and Ansys Mechanical's Ansys Workbench in the same environment. As a result of analysis, 3D magnetic nonlinear behavior of this three-phase autotransformer and thermal effects of ferromagnetic core can be seen. In addition, the magnitude of the magnetic field was calculated, problematic regions were determined, and total core losses for different stress levels of the same transformer were obtained.